MAKNA CINTA TUHAN DAN KONSEP TENTANG ALAM DALAM PUISI D. ZAWAWI IMRON - Abdul Wachid (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This paper discusses the poem of D. Zawawi Imron were revealedabout the nature’s religiosity using semiotics as interpretation methods.The universe is understood in relation to the transcendent reality andGod-centered. D. Zawawi Imron’s worldview embodied in I-lyrics representationthat can be referenced in the Qur'an and the Hadith, related tothe relationship between human beings, the universe, and God. God manifestin the light of the heavens and the earth are manifested in variousforms, through nature and His names. In addition, the poem there is ameaning to life harmony by recognizing the existence and greatness ofGod, both in the universe and in human beings themselves.